Use of Outpatient-Derived COVID-19 Convalescent Plasma in COVID-19 Patients Before Seroconversion - Wirz, Oliver F.; Röltgen, Katharina; Stevens, Bryan A.; Pandey, Suchitra; Sahoo, Malaya K.; Tolentino, Lorna; Verghese, Michelle; Nguyen, Khoa; Hunter, Molly; Snow, Theo Thomas; Singh, Abhay Raj; Blish, Catherine A.; et al. (Frontiers in Immunology, 2021)
Background: Transfusion of COVID-19 convalescent plasma (CCP) containing high titers of anti-SARS-CoV-2 antibodies serves as therapy for COVID-19 patients. Transfusions early during disease course was found to be beneficial. Lessons from the SARS-CoV-2 pandemic could inform early responses to future pandemics and may continue to be relevant in lower resource settings. We sought to identify factors correlating to high antibody titers in convalescent plasma donors and understand the magnitude and pharmacokinetic time course of both transfused antibody titers and the endogenous antibody titers in transfused recipients. Methods: Plasma samples were collected up to 174 days after convalescence from 93 CCP donors with mild disease, and from 16 COVID-19 patients before and after transfusion. Using ELISA, anti-SARS-CoV-2 Spike RBD, S1, and N-protein antibodies, as well as capacity of antibodies to block ACE2 from binding to RBD was measured in an in vitro assay. As an estimate for viral load, viral RNA and N-protein plasma levels were assessed in COVID-19 patients. Results: Anti-SARS-CoV-2 antibody levels and RBD-ACE2 blocking capacity were highest within the first 60 days after symptom resolution and markedly decreased after 120 days. Highest antibody titers were found in CCP donors that experienced fever. Effect of transfused CCP was detectable in COVID-19 patients who received high-titer CCP and had not seroconverted at the time of transfusion. Decrease in viral RNA was seen in two of these patients. Conclusion: Our results suggest that high titer CCP should be collected within 60 days after recovery from donors with past fever. The much lower titers conferred by transfused antibodies compared to endogenous production in the patient underscore the importance of providing CCP prior to endogenous seroconversion.